Evolution of Human Immunodeficiency Virus Type 1 (HIV-1) Resistance Mutations in Nonnucleoside Reverse Transcriptase Inhibitors (NNRTIs) in HIV-1-Infected Patients Switched to Antiretroviral Therapy without NNRTIs - Joly, Véronique (American Society for Microbiology, 2004)
We studied the evolution of nonnucleoside reverse transcriptase inhibitor (NNRTI) resistance mutations among 29 human immunodeficiency virus type 1 (HIV-1)-infected patients who experienced virologic failure when receiving an NNRTI-containing regimen (nevirapine, delavirdine, or efavirenz) and subsequently switched to antiretroviral therapy without NNRTIs. Genotypic resistance was determined from plasma samples collected at the time of NNRTI withdrawal (baseline) and during follow-up. At baseline, 83% of patients had more than two thymidine analog resistance mutations (TAMs), and all had NNRTI resistance mutations. Mutations at codons 103, 181, and 190 were found in 62, 62, and 34% of the patients, respectively. Follow-up samples were available after a median time of 6 months in all patients and at 12 months in 22 patients. The mean number of resistance mutations to NNRTIs was significantly lower at months 6 (1.34 ± 1.04) and 12 (1.18 ± 1.05) than at month 0 (2.03 ± 1.02) (P < 0.009). The percentages of patients with at least one NNRTI resistance mutation were 100, 76, and 73% at baseline, month 6, and month 12, respectively (P < 0.0044). Overall, 70% of the patients had a mutation at codon 103 or 181 at month 12. The mean number of TAMs did not vary significantly during follow-up. Our data show that, in the context of maintained antiretroviral therapy, NNRTI resistance mutations persist in two-thirds of the patients in spite of NNRTI withdrawal. These results argue for the low impact of NNRTI resistance mutations on viral fitness and suggest that resistance mutations to different classes of drugs are associated on the same genome, at least in some of the resistant strains.